2016
DOI: 10.1111/cch.12311
|View full text |Cite
|
Sign up to set email alerts
|

Why do families enrol in paediatric weight management? A parental perspective of reasons and facilitators

Abstract: Healthcare providers might optimize enrolment in paediatric weight management by being proactive in referring families, discussing the advantages of the recommended care to meet treatment expectations and providing support to overcome enrolment barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Consistent with previous research showing that children’ motivation for treatment facilitates enrollment, we found that this factor also facilitated continued attendance. This finding is also aligned with PWM guidelines encouraging health services providers to assess and enhance families' motivation for treatment before and after care is commenced …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous research showing that children’ motivation for treatment facilitates enrollment, we found that this factor also facilitated continued attendance. This finding is also aligned with PWM guidelines encouraging health services providers to assess and enhance families' motivation for treatment before and after care is commenced …”
Section: Discussionsupporting
confidence: 90%
“…Parents' concerns about their children's weight and health can help to motivate enrolment in treatment for PWM. 19,20 Our study showed that these concerns are also important drivers of continued Although "success" in PWM has been traditionally measured in terms of improvements in weight status, [21][22][23] our data suggest that families hold a broader definition of success, which aligns with contemporary views of managing paediatric obesity 23,24 and previous research on parental motivation (eg, help improve children's psychosocial health)…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In some cases, professional referrals have provided an efficient and effective pathway to enrolment in a program (i.e. in relation to numbers enrolled and cost) [1922] however, the overall attendance of families professionally referred has been shown to be less when compared to those who are self-referred [19, 21]. …”
Section: Introductionmentioning
confidence: 99%